Analisis Pendapatan Usaha Minyak Kelapa Pcp Rotat Kecamatan Nita Kabupaten Sikka - Taras Iawan Saputera Wanda; Imakulata Dewi Malina (Jurnal Ilmiah Wahana Pendidikan, 2022)
Crude coconut oil as one of the processed coconut products is a modern product of coconut fruit that has a variety of benefits. CCO is able to boost immunity and treat various diseases. Besides that in the process of making it easy so that it can be done by siaa only. Crude Coconut Oil is a potential venture to be developed. This research aims to find out the income and feasibility of PCP Rotat coconut oil business in Nita District, Sikka Regency. The analysis tool used in this study is the analysis of revenues of coconut oil businesses with data sources, namely primary data and secondary data. The results of the analysis showed that the income obtained at the research site was Rp -727,768,000. The R/C ratio of the coconut oil business is 0.016 meaning that less than 1 then the PCP Rotat coconut oil business suffered a loss